2022
DOI: 10.1155/2022/7958375
|View full text |Cite
|
Sign up to set email alerts
|

Neurohumoral Profiles and Childhood Adversity of Patients with Multisomatoform Disorder and Pain as the Leading Bodily Symptom

Abstract: Objective. Patients suffering from chronic pain often present with multifactorial underlying conditions, sometimes without concrete pathological physical findings. Functional somatic syndromes (FSS) and somatoform disorders show a high prevalence of 8-20% and are often associated with adverse childhood experiences (ACE) and chronic stress. As many different FSS have overlapping symptoms, the concept of multisomatoform disorder (MSD) has been introduced as an encompassing concept. We hypothesize that a common n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…However, a few studies applying short-term cortisol measures do exist, including a recent case–control study on 151 adult mainly female patients with multi-system FSD. This study found reduced levels of serum cortisol and a negative correlation between cumulative chronic stress scores and serum cortisol in females, thus providing preliminary support for the involvement of chronic stress and hypocortisolism in multi-system FSD [ 53 ]. Alternatively, the heterogeneous results of existing studies investigating HPA axis dynamics in FSD could suggest that the primary phenomenon involves a dysregulated pattern of hormone secretion, resulting in an attenuated diurnal variation of cortisol and a reduced responsiveness of the HPA axis but limited deviations in long-term cortisol levels as reflected in HCC [ 13 , 15 , 17 ].…”
Section: Discussionmentioning
confidence: 63%
“…However, a few studies applying short-term cortisol measures do exist, including a recent case–control study on 151 adult mainly female patients with multi-system FSD. This study found reduced levels of serum cortisol and a negative correlation between cumulative chronic stress scores and serum cortisol in females, thus providing preliminary support for the involvement of chronic stress and hypocortisolism in multi-system FSD [ 53 ]. Alternatively, the heterogeneous results of existing studies investigating HPA axis dynamics in FSD could suggest that the primary phenomenon involves a dysregulated pattern of hormone secretion, resulting in an attenuated diurnal variation of cortisol and a reduced responsiveness of the HPA axis but limited deviations in long-term cortisol levels as reflected in HCC [ 13 , 15 , 17 ].…”
Section: Discussionmentioning
confidence: 63%
“…Other studies have reported increased leptin levels in migraine [ 49 ], pelvic pain in endometriosis [ 50 ], lipedema [ 27 ], low back pain [ 51 ], and multisomatoform disorder (MSD) [ 52 ]. Leptin levels have been reported to be reduced when weight is lost [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the potential for a history of adversity in people with chronic pain is an opportunity to consider management options. 31 , 36 , 48 Further research into how this information is obtained should be undertaken to allow for consistency of approach. A history of childhood adversity should be considered in the assessment of chronic pain so that relevant management options can be determined (although further research into effective interventions is also required).…”
Section: Discussionmentioning
confidence: 99%